PENGARUH SILIKA SEKAM PADI PADA SINTESIS KOMPOSIT Fe3O4/KITOSAN/SiO2 DAN UJI ADSORPSI LOGAM Cu(II) - Verry Andre Fabiani; Ristika Oktavia Asriza (JEDCHEM (JOURNAL EDUCATION AND CHEMISTRY), 2022)
Synthesis of Fe3O4/chitosan/SiO2 composites has been carried out. This study observed the effect of rice husk silica on the synthesis of Fe3O4/Chitosan/SiO2 composites and the Cu (II) Metal Adsorption Test. The synthesis was carried out by synthesizing Fe3O4, preparing chitosan from rajungan shells, extracting silica from rice husks and synthesizing Fe3O4/chitosan/SiO2 Composite composites. Rice husk silica which was varied with a mass of 0.5; 0.75; and 1 gram. The results of XRD analysis showed the presence of Fe3O4 phase and SiO2 phase and crystalline structure. Composite adsorption test on Cu (II) metal showed the greatest adsorption efficiency with the addition of 1 gram of SiO2, which was 77.60 %.